The Impact of Problem Based Learning Methods on Long Jump Learning Outcomes for Primary School - Iqbal Husnayadi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. The aim of this study was to determine the impact of the problem-based learning approach on the educational outcomes of the Primary School long jump students. Materials and methods. This investigation employed a pre-experimental design experimental methodology. 37 children represented the study's population. With an average group size of 37 students, the study's sampling strategy was saturated sampling. The pretest, treatment, and posttest phases are used in data collection. The long jump test column is the tool utilized. Data analysis with the effect test (ttest). Results. The long jump capacity findings with the problem-based learning model with tcount=8.99>ttable=1.99 were calculated based on the data obtained. These results show that ha is accepted and ho is rejected, indicating a rise, when the difference between the pretest mean value of 51.85 and the posttest mean value of 66.36 is bigger, with a difference of 14.51 numbers if the difference is 28%. Conclusions. Students' psychomotor abilities are improved by the model problem-based learning because it allows students to concentrate on problem-solving as they are aware of the learning process's trouble spots right away.